PELATIHAN MANAGEMEN SENI DAN BUDAYA ACEH PASCA KONFLIK DAN TSUNAMI MELALUI KANTONG-KANTONG KESENIAN DI KABUPATEN BIREUEN ACEH - INDONESIA - Iswadi Iswadi (LPPM Universitas Al Muslim, 2018)
This article is concerned with the program of social service under title: workshop on arts and cultural management post conflict and tsunami through arts activities in Bireuen-Aceh. The objective of this program is to increase the cultural consciousness through one day workshop on arts and cultural management in relation to creative economic and the development of tourism in some districts of Bireuen-Aceh. It is realized that some products of arts and culture in Aceh must be maintained as well as possible through a better management. The methodology used here is descriptive qualitative method, by describing the result of the data analysis qualitatively. The result showed that conducted a good management toward some products of arts and culture, it will produce some economic adventages related to the creative economic in the context of tourism development. This condition will be an important thing to change the paradigm of the way of thinking in Acehnese society in general, where people still seem to have an orientation to be government officer.